Use of ICD-9-CM coding for identifying antibiotic prescriptions during hospitalization: a Delphi consensus model - Agnese Comelli; Camilla Genovese; Giulia Renisi; Luigia Scudeller; Martina Zanforlini; Giulia Macaluso; Arianna Mazzone; Antonio Muscatello; Giorgio Bozzi; Alessia Zoncada; Angelo Pan; Marianna Rossi; et al. (Elsevier, 2024)
Summary: A Delphi consensus-seeking procedure was conducted to validate a list of ICD-9-CM codes that could help identify hospital admissions in which antimicrobials are more likely to be prescribed. The panel agreed to include 2967 codes out of 16229 (18.28%). Such codes could support AMS strategies by large-scale monitoring of drug consumption.